2015
DOI: 10.1007/s12039-015-0941-8
|View full text |Cite
|
Sign up to set email alerts
|

A computational investigation of the photochemical oxaziridine and amide conversion process of open-chain conjugated nitrone with electron-withdrawing trifluoromethyl group on nitrogen

Abstract: This computational study investigates the photo-excitation process and subsequent photoproduct formation steps through non-radiative deactivation channels in open-chain conjugated N-substituted nitrone systems (model compounds of corresponding retinylnitrones) having electron-withdrawing groups on nitrogen. Calculations mostly based on CASSCF/6-31G* and CASMP2/6-31G* level of theories on a representative system with N-trifluoromethyl substituent have predicted initial photo-excitation to a planar singlet state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 68 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…In recent times, the photochemistry of open-chain acyclic N -alkyl nitrones has been extensively studied by Chattopadhyay and co-workers. This includes the chemopreventive retinyl nitrone (and their model compounds), fluorescent naphthyl nitrone, α-styryl nitrone, and some other open-chain nitrones, as well. Their comprehensive theoretical investigations have put forward the explanations of several unanswered questions related to these acyclic systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times, the photochemistry of open-chain acyclic N -alkyl nitrones has been extensively studied by Chattopadhyay and co-workers. This includes the chemopreventive retinyl nitrone (and their model compounds), fluorescent naphthyl nitrone, α-styryl nitrone, and some other open-chain nitrones, as well. Their comprehensive theoretical investigations have put forward the explanations of several unanswered questions related to these acyclic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Presence of nonradiative decay channels through surface crossings or avoided crossings between the low-lying states will be investigated. One of the major objectives of this work is to highlight the similarity or the difference in the photochemical behavior of our previously studied acyclic and currently studied cyclic nitrone systems. Overall, this work is going to be the first comprehensive approach toward revealing the photochemistry of the so far unexplored cyclic nitrone systems.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well-accepted now that conical intersections play a key role in numerous photochemical and photobiological events. One such example is the photochemical oxaziridine conversion reaction of nitrones which we have thoroughly studied in recent years. These studies were mostly done on the nitrone systems with alkyl substituents on nitrogen. Choice of alkyl substituents in these nitrones was primarily based on the experimentally observed fact that N -alkyl group in nitrones stabilizes the oxaziridine , while electron-withdrawing groups have an opposite effect. , Our complete active space self-consistent field (CASSCF)-based computational studies have further confirmed this experimental observation.…”
Section: Introductionmentioning
confidence: 99%
“…Photochemical reactions of nitrones have been thoroughly investigated by our group in the last few years . Various categories of acyclic and cyclic nitrones have been analyzed through quantum mechanical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Photochemical reactions of nitrones have been thoroughly investigated by our group in the last few years. [1][2][3][4][5][6] Various categories of acyclic and cyclic nitrones have been analyzed through quantum mechanical studies. Experimental results reported for these nitrones were clearly justified by these abinitio-based calculations.…”
Section: Introductionmentioning
confidence: 99%